Uso de indicadores chave de desempenho para avaliar sistemas de gestão - Sampaio, Paulo Alexandre da Costa Araújo (2015)
This research project intend to create knowledge in the area of management systems integration. The main goals were to ascertain the extent of which key performance indicators are useful and used by the companies to evaluate the efficiency of the management system and to establish a set of guidelines in order to help companies in the definition of performance indicators that support and lead organizations in the sense of effectiveness and efficiency of their management systems. In close collaboration with the leading Portuguese certification body – Associação Portuguesa de Certificação (APCER), twenty semi-structured interviews were conducted with the Lead Auditors with highest number of combined audits carried out in three-year period (2008-2010) and nine semi-structured interviews were conducted with personalities and entities with a relevant and active role in the field of management systems integration. After the interviews a set of case studies were carried out in companies with a certified Quality, Environment and Safety integrated management system. The main conclusions of this work point out the need of the development of transversal and sectoral methodologies and good practices that support organizations in the implementation and in the evaluation of the integration results. Furthermore, we were able to find out that the success of the management system integration depends on the motivation, involvement and commitment of the organization.